Pengendalian vektor malaria menggunakan bioinsektisida di habitat sungai pada musim kemarau di Kecamatan Kokap Kabupaten Klon Progo = Malaria vector control using bioinsecticide in the River Habitat during Dry Season ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Kokap sub-district is a hilly area. During dry season, the river flow is small water bodies are formed. Those water holding bodies are potential for Anopheles spp growth. Therefore, alternative control of malaria vector that is environmentally friendly, effective and efficient for the area. The aims of this study was to determine the difference of the killing power effect of bioinsecticides: B. thuringiensis H-14 of liquid formulation, B. thuringiensis H-14 of granule formulation, and B. sphaericus H-5a5b granule formulation on Anopheles spp. larvae density water holding during dry season. This was a quasi experimental study using a multiple time series frame design. The study was conducted in water holding bodies where Anopheles spp. develops in three rivers where larvae are found, in Kokap sub-district Kulonprogo regency in the special Province of Yogyakarta. The study started by distributions bioinsecticides: B. thuringiensis H-14 liquid formulation for 1 liter/ha dosage in 15 water holding bodies of 0.6-10.0 m2 in the Progo River